Amelioration of Phenol Formaldehyde Adhesive With Silicic Acid for Application in Plywood - Bhatt, Shweta; Tripathi, Sadhna; Khali, D. P. (Indian Forester, 2015)
Phenol formaldehyde adhesive is used in laminated as well as composite panels due to its good adhesion, high polymeric strength and excellent stability. The purpose of present study was to prepare plywood of good shear strength using silicic acid (2,3 and 4%) in phenol formaldehyde adhesive. The effect of silicic acid on plywood was evaluated by testing glue shear strength (GSS) of plywood in dry and wet conditions. The mycological test was also conducted in plywood to test its efficacy against white rot fungus (Trametes versicolor). Results revealed that shear strength of plywood was increased by adding silicic acid (2 and 3%) in adhesive, whereas by increasing the concentration of silicic acid (4%) the glue shear strength was reduced but still met the requirement of shear strength as per IS: 848. It was found that glue failure percentagewas also reduced after adding silicic acid in PF adhesive.